Faktor yang Mempengaruhi Pengelolaan Keuangan pada Mahasiswa Fakultas Ekonomi Universitas Batanghari - Hana Tamara Putri (Ekonomis: Journal of Economics and Business, 2022)
Using two Factor to determine the Financial Management using financial literacy and lifestyle factor, this study using 100 students of Economic Faculty. The data collection technique used a questionnaire. The data analysis technique is quantitative data. With multiple linear regression testing, classical assumption test, partial test (t) and simultaneous test (F) and the coefficient of determination. Testing the results of research data using the SPSS V.22.0 application with the results of financial literacy (X1) has a partial effect on financial management. And lifestyle (X2) has a partial effect on financial management and financial literacy and lifestyle simultaneously affect the financial management of students in the management study program of the economics faculty of Batanghari University. And the rest is influenced by other variables not examined.